(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Reading Thomas Hardy’s fiction is like travelling across the realm of Victorian society unfolding its various colourful layers to the traveller. The strength and beauty of Hardy’s fiction is primarily rested on his art of characterization which is deepened by both women characters and rustic ones. In fact, the most significant facet in the oeuvre of Hardy’s fiction is his portrayal of women characters through which one can easily have a trace of the socio-economic, socio-political and socio-familial norms of the society of his time. Reading his novels is like understanding the various prevailing sex-related issues, social bindings including marriage, the strong hold of man folk upon the society so called patriarchal hegemony and the sufferings of woman folks under these conventions in his Victorian society, so called Hardy’s Wessex world. Amidst these social conventions silently crept into the Wessex life a hugely important social movement or awakening of women presently known as feminism which emerged in Hardy’s England and took much attention of people and which requires a separate discussion so far realism in his novels is concerned. Moving in and around the Wessex territory Hardy observed the social life and in his writings gave vent to the feelings, cries and ambitions of the women folk living under pressure in the man ruled society.